Understanding Leadership in Second Language Acquisition within ‘The Big Five Model’ - Irene Siddique Nancy; Hassan, Syed M Ariful; Nawaz, Rukhsar Sanjaree; Priya, Zakia Romana (Environment-Behaviour Proceedings Journal, 2025)
This study explores the psychological traits of twenty second language learners focusing on their engagement and success in acquiring English as a Second Language. Using Lewis Goldberg’s Big Five Model, examine their personality traits to understand how these ideas influence their leadership in language acquisition. The analysis considers the interplay of "nature" and "nurture" in shaping learners’ flexibility and development. The mixture of qualitative and quantitative study features—nine males and eleven females—all in their early twenties, offering insights into individual differences in second language learning and the role of psychological factors in their endeavors.